Strategi Komunikasi Negosiasi Dalam Transaksi Jual Beli Ternak Pada Kelompok Tani Bumi Sinar Mukti Kabupaten Bandung - Meiyanti Nurchaerani; Ario Pamungkas; Alfian; Syahiid Hidayatullah Rizkyka Hartadhi; Agus Firmansyah (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Bumi Sinar Mukti Farmers Group in Bandung Regency faces communication problems in livestock buying and selling transactions rooted in high trust among members and a lack of structured negotiation communication understanding. Cases such as verbal agreements without documentation result in payment arrears lasting months, causing internal conflicts that threaten group solidarity. This community service aims to improve understanding and skills in negotiation communication and basic legal literacy in buying and selling transactions. The methods used included FGDs to explore root causes, negotiation communication training, and assistance in creating simple written agreements. Results showed increased member understanding of the importance of written agreements, assertive yet relationship-preserving negotiation techniques, and reduced potential for conflict due to miscommunication. In conclusion, strengthening negotiation communication and transaction literacy can be a sustainable solution for the harmony and economic sustainability of farmer groups.